1996
DOI: 10.1016/0014-5793(96)00152-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a recombinant proteinase 3, the autoantigen in Wegener's granulomatosis and its reactivity with anti‐neutrophil cytoplasmic autoantibodies

Abstract: Using the bnculovlrus/Insect cells system, we have expmmed n recombinant protelnase 3 (PR3) --the neutrophil.derived sedne protease autonntlgen In Wegener's gntnulomatosis --as a illyemyiated Intrncellular and membrane-associated protein, OIIgosnochnrldes accounted for the difference in molecular weights between recombinant (34 kDa) and neutrophiI-PR3 (29 kDn), Whereas rabbit-anti-PR3 igG recognized both recombinant and nentrophll-derlved PR3, autoantibodies from Wegener patient sent reeognl~l only neutrophil-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…The most recent report of rPR3 expression in a baculovirus system has confirmed that that the majority of c-ANCA recognize conformational epitopes on PR3, and that insect cells are not able to process rPR3 into a conformationally intact form [13]. To determine whether rPR3 expressed by HMC-1/ PR3 cells is recognized by c-ANCA, 40 consecutive serum samples that had previously been determined to be c-ANCA positive by standard IIF on neutrophil cytospin preparations [21] and control sera (5 normal, 5 anti-myeloperoxidase ANCA positive, 10 containing various patterns of ANA and 5 containing anti-mitochondrial antibodies) were obtained from the clinical laboratory.…”
Section: Recognition Of Rpr3 By C-anca Seramentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent report of rPR3 expression in a baculovirus system has confirmed that that the majority of c-ANCA recognize conformational epitopes on PR3, and that insect cells are not able to process rPR3 into a conformationally intact form [13]. To determine whether rPR3 expressed by HMC-1/ PR3 cells is recognized by c-ANCA, 40 consecutive serum samples that had previously been determined to be c-ANCA positive by standard IIF on neutrophil cytospin preparations [21] and control sera (5 normal, 5 anti-myeloperoxidase ANCA positive, 10 containing various patterns of ANA and 5 containing anti-mitochondrial antibodies) were obtained from the clinical laboratory.…”
Section: Recognition Of Rpr3 By C-anca Seramentioning
confidence: 99%
“…The expression of recombinant PR3 (rPR3) as a fusion protein in E. coli and in baculovirus systems failed to generate an enzymatically active recombinant product that is recognized by the majority of c-ANCA sera [11][12][13]. Thereby, these reports have confirmed that most c-ANCA recognize conformational epitopes of PR3.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different expression systems have been used to express recombinant PR3 (rPR3) variants [8][9][10][11][12]. Full length cDNA constructs encoding the PR3 zymogen cloned into baculovirus vectors have been expressed in Sf9 insect cells [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Full length cDNA constructs encoding the PR3 zymogen cloned into baculovirus vectors have been expressed in Sf9 insect cells [8][9][10]. It has been reported that the N-terminal activation dipeptide needs to be removed in vitro from the expressed protein in order to obtain the active enzyme with the N-terminal amino acid sequence Ile-ValGly-Gly [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation